Epigenetic regulation - Minárovits János (Advances in Experimental Medicine and Biology, 2016)
Some of the key epigenetic regulatory mechanisms appeared early during evolution, and the acquisition of novel epigenetic regulators apparently facilitated certain evolutionary transitions. In this short review we focus mainly on the major epigenetic mechanisms that control chromatin structure and accessibility in mammalian cells. The enzymes methylating CpG dinucleotides and those involved in the active demethylation of 5-metylcytosine (5mC) are outlined together with the members of the methyl binding protein (MBP) family that bind to and “interpret” the 5mC mark. The enzymes involved in reversible, covalent modifications of core histone proteins that affect chromatin structure are also described briefly. Proteins that build up Polycomb group (PcG) and Trithorax group (TrxG) protein complexes may also modify histones. By establishing heritable chromatin states, PcG and TrxG complexes contribute - similarly to cytosine methylation - to the transmission of cell type-specifi c gene expression patterns from cell generation to cell generation. Novel players involved in epigenetic regulation, including variant histones, pioneer transcription factors, long noncoding RNA molecules and the regulators of long-distance chromatin interactions are introduced as well, followed by the characterization of various chromatin types. © Springer International Publishing Switzerland 2016.